موافقة ومخالفة أبان بن تغلب لقراءة الجمهور في سورتي" النساء والمائدة" - الحواش، محمد بن أحمد بن محمد بن معيض Alhawash, Mohammed Bin Ahmed Bin Mohammed Bin Maid (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بدمنهور, 2019)
بحث بعنوان: "قراءة أبان بن تغلب موافقة ومخالفة وأثرها في التفسير" يشتمل على مقدمة ومبحثين وخاتمة، تحدثت في المقدمة، عن تعريف علم القراءات وأهميته، ثم افتتحت المبحث الأول بتعريف موجز لأبان بن تغلب أشرت فيه إلى مولده، ونشأته، ومصنفاته، وشيوخه، وتلاميذه، وأقوال العلماء فيه، ووفاته، ثم تعريف القراءات الشاذة لغة واصطلاحا، ونشأتها، وتدوينها، وأهم المصنفات فيها، وأعلام القراء فيها، وحكم الاحتجاج بها في الأحكام، والتفسير، ثم ختمت بالمبحث الثاني والأخير والذي جمعت فيه القراءات المروية عن أبان بن تغلب في سورة النساء، والمائدة، مبينا فيها ما وافق فيها الجمهور، أو خالفهم، وأثر ذلك في التفسير إن وجد، ثم الخاتمة مشتملة على: أهم النتائج والتوصيات، وثبت المصادر والمراجع، ثم الفهارس.
This research titled: “Reading Aban Bin Taleb: Agreeing, Disagreeing with and its Impact on Exegesis” includes an introduction, two sections and a conclusion. The introduction is about the definition of the discipline of readings and its importance. In the first section, it starts with a brief introduction on Aban ibn Tghleb containing his birth, upbringing, work, elders, disciples, the opinions of experts on him, and his death. Then, it is followed by the definition of abnormal readings in language and terminology, its origin, codification, the most important works, well-known readers, the ruling on invoking them in judgments, and exegesis. The second section shows a collection of narrated readings from Aban bin Tghalb in Chapters of Al-Fatihah, the Cow and Al-Imran, indicating where what the majority scholars agreed or disagreed with, and the impact of that on interpretation, if any. The research is concluded with the most important findings, recommendations, and a list of sources, references, and indexes.
Keywords: القرآن الكريم -- القراءات القرآنية -- القراءات الشاذة -- سورة النساء -- سورة المائدة -- أبان بن تغلب